2019
DOI: 10.2147/ott.s182525
|View full text |Cite
|
Sign up to set email alerts
|

<p>Bioinformatic analysis of miR-4792 regulates <em>Radix Tetrastigma hemsleyani</em> flavone to inhibit proliferation, invasion, and induce apoptosis of A549 cells</p>

Abstract: Background Radix Tetrastigma hemsleyani , a kind of Chinese medicinal herb, contains multiple medicinal ingredients and can exert a variety of pharmacological activities. Our previous study revealed that miR-4792 was significantly upregulated in Radix Tetrastigma hemsleyani flavone (RTHF)-treated A549 cells; however, the regulatory mechanism of RTHF-treated A549 cells remains unclear. Materials and methods In this study, we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Lung cancer is the only malignant tumor for which morbidity and mortality rates have been increasing in recent years (1). In addition, lung cancer has become the leading cause of cancer-associated mortality worldwide (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lung cancer is the only malignant tumor for which morbidity and mortality rates have been increasing in recent years (1). In addition, lung cancer has become the leading cause of cancer-associated mortality worldwide (1).…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is the leading cause of cancer-associated mortality, with ~1.35 million novel cases being diagnosed each year worldwide (1). A total of ~75-80% of lung cancer cases are non-small cell lung cancer (NSCLC), with the overall 5-year survival rate of 10% (2).…”
Section: Introductionmentioning
confidence: 99%
“…Sporothrix schenckii yeast induces robust activation of JNK, ERK1/2 and p38 MAPK in dendritic cells, which is related to IL-6 and TNF-α secretion. Recent study demonstrated that miR-4792 participates in the apoptotic induction of A549 cells by RTHF via MAPK pathway and determines the potential apoptotic mechanism [56]. In this study, we found that miR-4792 mimics/inhibitors did not signi cantly in uence EGFR expression at the transcription level, suggestive of translational regulation.…”
Section: Discussionmentioning
confidence: 55%
“…As a result, 162 miRNAs have been identified to display expression changes >1.2fold in RTHF-treated A549 cells. On the basis of the above research, Liu P. et al (2019) also find that miR-4792 may be involved in the inhibition of A549 cell proliferation and metastasis mediated by total flavones of TDG. Meanwhile, total flavones of TDG is to down-regulate the overexpression of miRNA in cancer, and also upregulate the expression of tumor suppressor miRNAs.…”
Section: Pharmacological Activities Anti-tumor Activitymentioning
confidence: 79%
“…As a result, 162 miRNAs have been identified to display expression changes >1.2-fold in RTHF-treated A549 cells. On the basis of the above research, Liu P. et al. (2019) also find that miR-4792 may be involved in the inhibition of A549 cell proliferation and metastasis mediated by total flavones of TDG.…”
Section: Pharmacological Activitiesmentioning
confidence: 79%